2002
DOI: 10.1128/jb.184.1.119-125.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PauB, a Novel Broad-Spectrum Plasminogen Activator from Streptococcus uberis

Abstract: A bovine plasminogen activator of atypical molecular mass (ϳ45 kDa) from Streptococcus uberis strain SK880 had been identified previously (L. B. Johnsen, K. Poulsen, M. Kilian, and T. E. Petersen. Infect. Immun. 67:1072-1078, 1999). The strain was isolated from a clinical case of bovine mastitis. The isolate was found not to secrete PauA, a bovine plasminogen activator expressed by the majority of S. uberis strains. Analysis of the locus normally occupied by pauA revealed an absence of the pauA open reading fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 35 publications
0
28
0
1
Order By: Relevance
“…Various virulence factors such as hyaluronic acid capsules (HasA, HasB, HasC) (9), plasminogen activator proteins (PauA and PauB) (10,11) and streptokinase (12), lactoferrin binding proteins (Lbp) (13), adhesion protein (SUAM) (14), CAMP factor (15), a surface dehydrogenase protein (GapC) (16), protein involved in the active transport of solutes essential for growth in milk (OppF) (17), and a lipoprotein receptor antigen responsible for acquisition of manganese during growth in milk (MtuA) (18) have been suggested to be associated with pathogenesis of IMI caused by S. uberis. The objective of the current study was to investigate genotypic variations and distribution of virulence-associated genes of S. uberis isolated from milk samples in northern Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Various virulence factors such as hyaluronic acid capsules (HasA, HasB, HasC) (9), plasminogen activator proteins (PauA and PauB) (10,11) and streptokinase (12), lactoferrin binding proteins (Lbp) (13), adhesion protein (SUAM) (14), CAMP factor (15), a surface dehydrogenase protein (GapC) (16), protein involved in the active transport of solutes essential for growth in milk (OppF) (17), and a lipoprotein receptor antigen responsible for acquisition of manganese during growth in milk (MtuA) (18) have been suggested to be associated with pathogenesis of IMI caused by S. uberis. The objective of the current study was to investigate genotypic variations and distribution of virulence-associated genes of S. uberis isolated from milk samples in northern Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that pauA, encoding a secreted plasminogen activator, was undergoing positive selection in itself renders this scheme unsuitable for the analysis of population structure and evolutionary relationships (38). Furthermore, it has been noted that in some isolates pauA may be absent or replaced by pauB, which encodes an alternate but unrelated plasminogen activator (35).…”
mentioning
confidence: 99%
“…A second plasminogen activator called PauB, with a molecular weight of 45 kDa, was identified by Johnsen et al (1999) in a S. uberis strain isolated from a case of clinical mastitis in Denmark [44]. Ward and Leigh (2002) determined the absence of the plasminogen activator PauA in this strain and found that pauB gene was present in the locus normally occupied by pauA [43]. The authors demonstrated its activity on bovine, ovine, equine, goat, porcine, rabbit and human plasminogen.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…Briefly, virulence factors includes: plasminogen activator proteins such as PauA and PauB and SK, resistance to phagocytosis presented by a hyaluronic acid capsule, CAMP factor, a surface dehydrogenase protein GapC, sortases, Opp proteins implicated in dynamic transport of solutes, lactoferrin binding proteins, and adherence and invasion of epithelial cells mediated by SUAM [42][43][44][45][46][47][48][49][50][51].…”
Section: Virulence Factorsmentioning
confidence: 99%